Textual and social aspects of accessing high school economics and management sciences (EMS) : a case study of literacy, learning and identity in a social semiotic domain - Kalil, Claudia (School of Education, 2024)
The focus in this study is on literacy and learning in Economics and Management Sciences (EMS). EMS comprises integrations of language, mathematics, social elements and practical actions. The research identified ways of constructing knowledge in the EMS genre and evaluated application of principles of effective literacy learning in learners' practices. The research asked therefore: what are the semiotic practices, communication exchanges, and accompanying learning activities in the EMS classroom studied, and how do these constitute a productive domain of learning for students? The research site was a girls-only High School located in a middle-class suburb. An ethnographic-style case study method was used. To gain access to the variability of social life in the site and discern layers of meaning there, relatively long periods were spent recording classroom interaction. The analysis was concerned with the building of textual and social meanings related to which semiotic systems were made relevant and how. Key theoretical resources used included the situated practice approach of the New Literacy Studies (NLS), sociocultural models of cognition, and Gee's (2003) classification of learning principles in a social semiotic domains framework. It was found that various modalities were used in the classes and the teacher's conscious attention to making links between the different modes of communication, the written numbers and the visual, modelled talking about, responding to and interpreting information from visual texts. Learning was co-operative and distributed across people and the technologies of language, writing and numbers. The learning environment was set up so that learners could in dialogue with the teacher discover elements of the domain in an active way. Literacy practices enacted in a framework of everyday activity made learning events embodied and hence apprenticeship-like. A weakly framed simulation assignment meant that control over learning was largely vested in the learners themselves. Students came to appreciate interrelations across multiple sign systems as a complex system; they learnt that learning involves critical thinking about the relationship between semiotic domains at a meta-level. A typical teaching strategy was to scaffold learning to help learners take on knowledge in degrees and build up a complex understanding of the EMS domain. At times the teacher assumed knowledge on the part of learners and this acted as an obstacle to learners accessing the EMS genre. In the course of learning specific elements of EMS literacy, learners became exposed to social events and individuals from outside of the classroom and school. The way learners reacted to and interacted with these discourses resulted in the creating of positionalities for themselves at that time, as South Africans, as rational 'scientists' or academics, and in relation to one another. Teacher feedback on recognition from authority figures of learners' specialist EMS knowledge facilitated learners seeing themselves as insiders who have a recognizable level of achievement in the EMS domain, and helped them to bridge from their earlier (less experienced) identities to new ones as 'experts' in the domain. Through the stockbroker simulation assignment learners could develop identities through feeling the emotions, values and beliefs and experiencing the actions of a real-world broker. They thus had a scaffold to support later literacy learning and experience. The study showed that students were actively and critically learning the semiotic systems of EMS, developing an identity as part of the social group attached to the EMS domain, and being prepared for learning in the domain and future learning. These facts mean that it is possible to evaluate the classes researched as being a productive domain for learning.